TINDAKAN HUKUM PEMERINTAH DAERAH KABUPATEN ROKAN HILIR DALAM AKSELERASI DESA TERTINGGAL DI KEPENGHULUAN TELUK PIYIAI PESISIR DESA SUNGAI AGAS TAHUN 2017-2020 - Tri Muliani; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Regional Government Legal Actions are actions taken by state administrative bodies or officials in carrying out their own regional government affairs. Acceleration of underdeveloped villages is an acceleration in making changes in speed within a certain time in a village whose community and territory are relatively less developed compared to other regions. Which is regulated in Rokan Hilir District Government Regulation Number 07 of 2015 concerning the Development of the Kepenghuluan Area. The formulation of the problem of this research is: How is the Legal Action of the Rokan Hilir District Government in the Acceleration of Disadvantaged Villages in Kepenghuluan Teluk Piyai Pesisir, Sungai Agas Village in 2017-2020? and Are the Factors Affecting the Legal Actions of the Rokan Hilir District Government in Accelerating Disadvantaged Villages in Kepenghuluan Teluk Piyai Pesisir, Sungai Agas Village Has Not Succeeded in 2017-2020? Downstream and the factors that influence the actions of the local government of Rokan Hilir regency in accelerating disadvantaged villages in Kepenghuluan Teluk Piyai Pesisir, Sungai Agas Village has not been successful in 2017-2020.               This research uses Government Law Action Theory. Government legal action is an action taken by a State Business Administration Agency or Official in carrying out government affairs. In carrying out government actions, it must be based on existing laws and regulations. The research method used in this research is qualitative research. Then this type of research is in the form of a descriptive qualitative. Research location in Kepenghuluan Teluk Piyai Pesisir, Kubu District, Rokan Hilir Regency. The results of the study are that in the implementation of legal action by the local government of Rokan Hilir Regency in the acceleration of disadvantaged villages in Kepenghuluan Teluk Piyai Pesisir, Sungai Agas Village in 2017-2018. In this case, the government implements the Rokan Hilir Regency Regional Regulation Number 07 of 2015 concerning the Development of the Kepenghuluan Area, in collaboration with the Rokan Hilir Regency Community and Village Empowerment Service (PMD). Then also in the implementation of the Rokan Hilir District Government Legal Actions, there are factors that affect the Rokan Hilir District Government Legal Actions in Accelerating Disadvantaged Villages in 2017-2020 Not Yet Success. namely there are Internal and External Factors besides these factors there is also in exercising their authority for the benefit of the community at large not only for their own interests such as empowerment programs in the field of government, health development, village economic empowerment, majelis taklim and mutual cooperation in accordance with the main tasks and functions from the village leader, and all is done to empower the people of the Teluk Piyai Pesisir islands in each hamlet. Keywords: Local Government Legal Actions, Underdeveloped Village Acceleration.